Statecraft by Stealth : Secret Intelligence and British Rule in Palestine - Wagner, Steven, 1985- (Book collections on Project MUSE., 2019)
"This book is about Britain's use of intelligence in Palestine from the beginning of the occupation during WWI, through riots and disturbances of the 1920s, the revolt of the 1930s, and the beginning of WWII"--